2018
DOI: 10.1159/000493358
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Infants with Therapeutic Hypothermia after Perinatal Asphyxia and Early-Onset Sepsis

Abstract: Background: Animal models suggest that neuroprotective effects of therapeutic hypothermia (TH) after perinatal asphyxia are reduced in infants with early-onset sepsis. Objectives: To assess the outcome of infants with perinatal asphyxia, neonatal encephalopathy, and TH in the presence of early-onset sepsis. Methods: In a retrospective cohort of 1,084 infants with perinatal asphyxia and TH, the outcome of 42 infants (gestational age 36.1–42.6 weeks and birth weight 2,280–5,240 g) with proven sepsis (n = 14) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 29 publications
4
38
2
3
Order By: Relevance
“…A single-center study reported that TH was not neuroprotective in asphyxiated newborns with proven bacterial chorioamnionitis, despite antibiotic treatment (Wintermark et al, 2010). Recently, a retrospective analysis from the Netherlands and Belgium reported that outcome in newborns with perinatal asphyxia and proven culture-positive sepsis did not significantly differ from outcome of infants with perinatal asphyxia without sepsis (Hakobyan et al, 2018). However, the number of infants with culture-positive sepsis involved in both studies was very low.…”
Section: Discussionmentioning
confidence: 99%
“…A single-center study reported that TH was not neuroprotective in asphyxiated newborns with proven bacterial chorioamnionitis, despite antibiotic treatment (Wintermark et al, 2010). Recently, a retrospective analysis from the Netherlands and Belgium reported that outcome in newborns with perinatal asphyxia and proven culture-positive sepsis did not significantly differ from outcome of infants with perinatal asphyxia without sepsis (Hakobyan et al, 2018). However, the number of infants with culture-positive sepsis involved in both studies was very low.…”
Section: Discussionmentioning
confidence: 99%
“…Medical files were reviewed for demographics. Some data of these infants have been published in previous studies [11][12][13][14][15][16]. The severity of NE was assessed by analysis of the aEEG background patterns in the hour before start of hypothermia and clinical grading tools documented in the electronic health care system, and a comparison was made between infants treated from February 2008 until October 2012 (period 1) and those treated from November 2012 until July 2017 (period 2).…”
Section: Data Collectionmentioning
confidence: 99%
“…Anaerobic glycolysis and lactic acidosis will ensue. Neonatal hypoxic ischemic encephalopathy refers to the neurologic sequelae of perinatal asphyxia [2,3].…”
Section: Introductionmentioning
confidence: 99%